Pan‐Trk immunohistochemistry is a sensitive and specific ancillary tool for diagnosing secretory carcinoma of the salivary gland and detecting ETV6–NTRK3 fusion. Issue 3 (11th December 2019) - Xu, Bin; Haroon Al Rasheed, Mohamed R; Antonescu, Cristina R; Alex, Deepu; Frosina, Denise; Ghossein, Ronald; Jungbluth, Achim A; Katabi, Nora
Abstract : Aims: Secretory carcinoma (SC) of the salivary gland typically harbours ETV6 – NTRK3 fusion, which can be utilised clinically to assist with diagnosis. Pan‐Trk inhibitor therapy has demonstrated drastic responses in patients with NTRK ‐translocated tumours, including SC. Pan‐Trk immunohistochemistry (IHC) is emerging as a sensitive and specific tool for detecting NTRK1, NTRK2 and NTRK3 fusions in various cancers. We aimed to establish the specificity and sensitivity of pan‐Trk IHC in diagnosing SC and detecting ETV6 – NTRK3 fusion. A literature review on the utility of pan‐Trk IHC was conducted. Methods and results: Pan‐Trk IHC was performed on 83 salivary gland neoplasms (29 SCs and 54 non‐SCs). ETV6 – NTRK3 fusion status was established in 25 cases. With any staining (nuclear or cytoplasmic) as a positive threshold, the sensitivity and specificity of pan‐Trk IHC were 90% and 70% in diagnosing SC, and 100% and 0% in detecting NTRK3 fusion. When only pan‐Trk nuclear staining was considered as positive, the sensitivity and specificity were 69% and 100% in diagnosing SC, and 92% and 100% in detecting NTRK3 fusion. Conclusions: Nuclear pan‐Trk IHC is highly specific for SC diagnosis, with a specificity approaching 100%, making it a useful and precise diagnostic tool for differentiating SC from its histological mimics. On the other hand, any pan‐Trk staining (nuclear or cytoplasmic) is highly sensitive for SC, and can serve as an attractive, cheap, fast and accessible screening tool for selecting patients to undergo confirmative molecular testing for clinical trials using TRK inhibitors.